Photodynamic therapy with methyl aminolevulinate in the treatment of basal cell carcinoma - A. A. Kubanov; I. N. Kondrakhina; N. V. Gribanov (Vestnik Dermatologii i Venerologii, 2017)
The article presents the results of the studies on the effectiveness of treatment basal cell carcinoma of the skin with photodynamic therapy with 5-aminolevulinic acid and methyl aminolevulinate. The results of the comparing trials between photodynamic therapy with methyl aminolevulinate and different other treatment modalities are presented.